2022
DOI: 10.1101/2022.02.23.22271417
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Resident microbes shape the vaginal epithelial glycan landscape

Abstract: Epithelial cells are covered in carbohydrates. This glycan coat or glycocalyx interfaces directly with microbes, providing a protective barrier against potential pathogens. Bacterial vaginosis is a condition associated with adverse health outcomes in which bacteria reside in direct proximity to the vaginal epithelium. Some of these bacteria, including Gardnerella, produce glycosyl hydrolase enzymes. However, glycans of the vaginal epithelial surface have not been studied in detail. Here we elucidate key charac… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 106 publications
2
5
0
Order By: Relevance
“…5g,h ). Importantly, similar changes in sialylated O-glycans have been previously observed in BV-associated mucus in vivo 30,90 . The loss of sialic acids in the mucus may reduce interactions between mucin molecules and contribute to the changes in the physical properties of mucus (e.g., lower viscosity, decreased fern branching) that we observed in the Cervix Chip.…”
Section: Resultssupporting
confidence: 82%
“…5g,h ). Importantly, similar changes in sialylated O-glycans have been previously observed in BV-associated mucus in vivo 30,90 . The loss of sialic acids in the mucus may reduce interactions between mucin molecules and contribute to the changes in the physical properties of mucus (e.g., lower viscosity, decreased fern branching) that we observed in the Cervix Chip.…”
Section: Resultssupporting
confidence: 82%
“…The removal of sialic acids renders mucins more vulnerable to further degradation by glycosyl hydrolases and proteases ( 63 ). A recent paper showed that recombinant sialidases of Gardnerella species led to desialylation of glycans in VK2/E6E7 and induced pathways of cell death, differentiation, and inflammatory responses ( 64 ). Therefore, these enzymes are important virulence factors that can contribute to the establishment and development of BV.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these combined observations, we propose that P. timonensis may be an initial colonizer of the vaginal epithelium and does not require an established G. vaginalis biofilm. After attachment, the high sialidase and fucosidase activity of P. timonensis at the vaginal epithelial surface removes the protective terminal glycans of the glycocalyx likely creating new binding sites for secondary colonizers ( 64 , 75 ) and enhancing bacterial colonization of the upper parts of the FRT ( 76 ).…”
Section: Discussionmentioning
confidence: 99%
“…Though we did not observe inhibition of GvNanH3 by Zanamivir in our experimental setup, it is possible that this enzyme can be partially inhibited as was previously demonstrated 31 . In an accompanying paper substrates such as human vaginal epithelial cell surface glycans 33 , glycan arrays 34 , or in more complex or natural settings 35,18 .…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that Gv NanH4 acts intracellularly on an as-yet-uncharacterized substrate given its lack of a signal peptide, or is inactive, similar to the Group B Streptococcus sialidase NonA 28 . Future work should examine sialidase activity towards additional substrates such as human vaginal epithelial cell surface glycans 33 , glycan arrays 34 , or in more complex or natural settings 35,18 .…”
Section: Discussionmentioning
confidence: 99%